Aksi Kolektif Perempuan Nelayan Puspita Bahari di Pesisir Demak: Membangun Solidaritas untuk Transformasi Sosial - Atikah, Amalia Risti; Siscawati, Mia; Adelina, Shelly (Jurnal Perempuan, 2025)
Fisherwomen on the coast of Demak face various gender injustice amidst environmental crises and public policies that lack gender responsiveness. The Puspita Bahari community serves as a platform for fostering solidarity, advocacy, and grassroots leadership among these women fishers. This study was conducted in three villages supported by Puspita Bahari-Morodemak, Margolinduk, and Purworejo-located in the Bonang sub-district of Demak. By integrating the analysis of spatial, temporal, and violence dimensions (STV) within the feminist everyday political economy framework (Elias & Rai 2018) with the theoretical lens of collective action (Kabeer 2020), this paper examines how Puspita Bahari's collective action resists marginalisation and simultaneously promotes social transformation in the daily lives of coastal women. The research underscores the importance of recognising fisherwomen as agents of change, endowed with local knowledge and collective strength, in realising gender-just development. Incorporating their voices into policymaking processes is crucial for meaningful and sustainable social transformation